2018
DOI: 10.3390/mi9110583
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanically-Adaptive Polymer Nanocomposite-Based Intracortical Probe and Package for Chronic Neural Recording

Abstract: Mechanical, materials, and biological causes of intracortical probe failure have hampered their utility in basic science and clinical applications. By anticipating causes of failure, we can design a system that will prevent the known causes of failure. The neural probe design was centered around a bio-inspired, mechanically-softening polymer nanocomposite. The polymer nanocomposite was functionalized with recording microelectrodes using a microfabrication process designed for chemical and thermal process compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…It was shown that the acute FBR characteristic of the mechanically adaptive MEA was similar to that seen from a permanently stiff MEA, but over time, the mechanically adaptive MEA resulted in a less severe FBR compared to stiff MEAs. In a study performed by Hess‐Dunning and Tyler, MEAs composed of biomimetic mechanically softening polymer nanocomposite were monitored for device and recording failure over the course of several weeks. MEA recording signals remained stable throughout the entire study.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the acute FBR characteristic of the mechanically adaptive MEA was similar to that seen from a permanently stiff MEA, but over time, the mechanically adaptive MEA resulted in a less severe FBR compared to stiff MEAs. In a study performed by Hess‐Dunning and Tyler, MEAs composed of biomimetic mechanically softening polymer nanocomposite were monitored for device and recording failure over the course of several weeks. MEA recording signals remained stable throughout the entire study.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…Nevertheless, various modifications to MEAs have been shown to be highly successful in reducing the resulting FBR following MEA insertion and improving their performance. Applying modifications to surface chemistry, topography,59a,61,67b stiffness, and geometry [81,86,90a] of MEAs have all been shown to be highly promising for improving MEA biocompatibility.…”
Section: Future Outlookmentioning
confidence: 99%
“…[58] Just as a flexible material like polyimide cannot penetrate a jellylike substance as easily or as precisely as a needle, so too do neuroimplantable devices based on highly flexible materials or biomaterials require temporary stiffening during implantation. This dynamic stiffness can be achieved by using materials that naturally change stiffness when transitioning from dehydrated to hydrated conditions-such as collagen, [58] poly(vinyl acetate) (PVAc), [127] PEG, [128] silk, [129] carboxy-methylcellulose, [130] and sucrose gel [131] -or upon removal of a temporary, pressurized liquid stiffening agent such as gallium. [132] Besides designing probes with materials of tunable stiffness, another method for implantation of flexible probes utilizes a stiff "shuttle" for delivery of the probe to the target location.…”
Section: Implantation-related Risk Factorsmentioning
confidence: 99%
“…[153] Furthermore, neural damage due to implantation-related trauma, as discussed in Section 3, and rigidity of probe forms, as discussed in Section 2, is an additional issue. [140] It is possible that improved material properties for lead fixation at the target site-including rigid nanostructures, [154] reinforced silk scaffolds, [129,155] and hydration-dependent stiffness [52,58,127,128,130,131] -may help to reduce such risks.…”
Section: Intracerebral Risk Factorsmentioning
confidence: 99%
“…Various research groups have addressed these issues by introducing unique features which are added to conventional shank-type cortical arrays through specially devised microfabrication techniques. As illustrated in Figure 1B, these efforts have resulted in a variety of microelectrode arrays featuring various non-conventional characteristics, including: (1) multi-sided arrays to avoid shielding and increase the recording volume [132,133,134,135,136,137,138,139,140,141]; (2) tube-type or cylindrical probes for three-dimensional (3D) recording, deep insertion and multi-modality capabilities [142,143,144,145,146,147,148,149,150]; (3) folded arrays for high conformability and 3D recording [151,152,153,154]; (4) self-softening or self-deployable probes for minimized tissue damage and an extension of the recording site beyond the gliosis [155,156,157,158,159,160,161,162,163,164,165,166,167,168]; (5) mesh- or thread-like arrays to minimize glial scarring and immune response levels [169,170,171,172,173,174,175,176,177,178,179,180,181]; (6) nanostructured probes to reduce the immune response [182,183,184,…”
Section: Introductionmentioning
confidence: 99%